2021
DOI: 10.1186/s13148-021-01154-x
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferase inhibitors combination therapy for the treatment of solid tumor: mechanism and clinical application

Abstract: DNA methylation, an epigenetic modification, regulates gene transcription and maintains genome stability. DNA methyltransferase (DNMT) inhibitors can activate silenced genes at low doses and cause cytotoxicity at high doses. The ability of DNMT inhibitors to reverse epimutations is the basis of their use in novel strategies for cancer therapy. In this review, we examined the literature on DNA methyltransferase inhibitors. We summarized the mechanisms underlying combination therapy using DNMT inhibitors and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 136 publications
0
75
0
Order By: Relevance
“…As a key component of post-transcriptional modification, DNA methylation has been intensively reported to be involved in the regulation of cancer-associated genes [ 36 , 37 ]. In our study, we found that the methylation level of all the GSDMs members is significantly reduced in HCC tissues, which puts us in mind of the increased expression of GSDMs in HCC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…As a key component of post-transcriptional modification, DNA methylation has been intensively reported to be involved in the regulation of cancer-associated genes [ 36 , 37 ]. In our study, we found that the methylation level of all the GSDMs members is significantly reduced in HCC tissues, which puts us in mind of the increased expression of GSDMs in HCC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a siRNA or antagonist against DNMT1 in U251 and U87 cells was shown to decrease the methylation level of the promoter region of miR-338-5p-5p, upregulate miR-338-5p expression, and finally downregulate ETS-1 expression. Among the four types of DNA methyltransferases, DNMT1 not only participates in the normal methylation process but also induces the silencing of tumor suppressors via hypermethylation of their promoter regions ( 62 , 63 ). The main function of DNMT3 (DNMT3a and DNMT3b) is de novo methylation in the early stage of embryonic development, whereas DNMT2 (also known as tRNA aspartic acid methyltransferase 1) is classified as an RNA methylase ( 64 – 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the 6-month PFS rate was significantly higher in patients treated with the combination (37%) compared to control treatments (11%), with the authors noting that these results suggest that a subgroup of HGSOC patients may benefit from the combination therapy. To date, DNMTis are the epigenetic modulators that have progressed the furthest in clinical trials, with next-generation DNMTis that confer less severe and dose-limiting side effects being investigated [81].…”
Section: Dna Methyltransferase Inhibitors (Dnmti)mentioning
confidence: 99%
“…These DNMT inhibitors (DNMTi) are cytosine analogues which are incorporated into the DNA strand during replication and covalently bind to DNMTs, making them inactive. As a result of this decrease in DNMT activity, CpG sites which were previously methylated become unmethylated during cell replication, and transcription of genes previously silenced due to promoter hypermethylation is increased [ 80 , 81 ]. Two DNMTis, azacitidine (5-azacitidine) and decitabine (5-aza-2′-deozycitidine), are approved for use in treating myelodysplastic syndrome [ 6 , 80 ], with a second-generation DNMTi, guadecitabine, currently being tested in clinical trials [ 82 , 83 , 84 ].…”
Section: Current Treatment With Epigenetic Modifiers Targeting Chemoresistance In Hgsocmentioning
confidence: 99%
See 1 more Smart Citation